Microtus abbreviatus Miller 1899 ... - Don E. Wilson; Russell A. Mittermeier; Thomas E. Lacher, Jr (Lynx Edicions, 2017)
130. Insular Vole Microtus abbreviatus French: Campagnol de Saint-Matthew / German: Inselwiihimaus / Spanish: Topillo de San Mateo Other common names: St. Matthew Island Vole Taxonomy. Microtus abbreviatus G. S. Miller, 1899, Hall Island, Bering Sea, Alaska, USA. Two subspecies are recognized. Subspecies and Distribution. M.a.abbreviatusG.S.Miller,1899—knownonlyfromthetypelocalityonHallI,Alaska M. a. fisheri Merriam, 1900 — known only from the type locality on St. M.a. I, Alaska. Descriptive notes. Head-body 111-146 mm, tail 25-32 mm, hindfoot 22-24 mm; weight 45-79 g. An adult Insular Vole has brown dorsum and is pale yellowish laterally and on rump, ear tips, and face. Belly furis lighter bufty color. Habitat. Rocky and willow (Salix, Salicaceae) patches of tundra. On St. Matthew Island, the Insular Vole is most abundant in moist lowlands and on lower slopes. Burrows are in well-vegetated rocky outcroppings. It is not found in dry lowlands or in areas with much standing water. Food and Feeding. Diet is ... : Published as part of Don E. Wilson, Russell A. Mittermeier & Thomas E. Lacher, Jr, 2017, Cricetidae, pp. 204-535 in Handbook of the Mammals of the World – Volume 7 Rodents II, Barcelona :Lynx Edicions on page 334, DOI: 10.5281/zenodo.6707142 ...